Measuring open defecation in India using survey questions: evidence from a randomised survey experiment - Sujatha Srinivasan; Sangita Vyas; Nikhil Srivastav; Divya Mary; Neeta Goel; Ajaykumar Tannirkulam; Radu Ban; Dean Spears; Diane Coffey (BMJ Open)
Objectives To investigate differences in reported open defecation between a question about latrine use or open defecation for every household member and a household-level question.Setting Rural India is home to most of the world’s open defecation. India’s Demographic and Health Survey (DHS) 2015–2016 estimates that 54% of households in rural India defecate in the open. This measure is based on a question asking about the behaviour of all household members in one question. Yet, studies in rural India find substantial open defecation among individuals living in households with latrines, suggesting that household-level questions underestimate true open defecation.Participants In 2018, we randomly assigned latrine-owning households in rural parts of four Indian states to receive one of two survey modules measuring sanitation behaviour. 1215 households were asked about latrine use or open defecation individually for every household member. 1216 households were asked the household-level question used in India’s DHS: what type of facility do members of the household usually use?Results We compare reported open defecation between households asked the individual-level questions and those asked the household-level question. Using two methods for comparing open defecation by question type, the individual-level question found 20–21 (95% CI 16 to 25 for both estimates) percentage points more open defecation than the household-level question, among all households, and 28–29 (95% CI 22 to 35 for both estimates) percentage points more open defecation among households that received assistance to construct their latrines.Conclusions We provide the first evidence that individual-level questions find more open defecation than household-level questions. Because reducing open defecation in India is essential to meeting the Sustainable Development Goals, and exposure to open defecation has consequences for child mortality and development, it is essential to accurately monitor its progress.Trial registration number Registry for International Development Impact Evaluations (5b55458ca54d1).